A review of X-ray computed tomography of concrete and asphalt construction materials. (28th February 2019) - du Plessis, Anton; Boshoff, William P.
Highlights: The use of X-ray microCT for concrete and asphalt building materials is reviewed. Successful applications of this technique to concrete and asphalt materials are summarized. Insight into the current capabilities and state of the art is provided. Newly developed methods are discussed and demonstrated. Suggestions are made for sampling and scan strategies for different analysis types. Abstract: The microstructural details of concrete and asphalt construction materials are crucial in understanding and improving their material properties for structural applications in civil engineering. Various destructive and non-destructive test methods are widely used in this field, but the use of non-destructive X-ray micro computed tomography is still widely under-estimated and the capabilities not yet fully appreciated. This review summarises the successful applications of this technique to concrete and asphalt materials to date and thereby provides insight into the current capabilities and state of the art. The review is structured according to the different types of analyses possible, and include examples of each, which helps to demonstrate the potential of the technique as applied to these types of structural materials. The recent growth in the use of the technique is related to its increased accessibility and newly developed methods which are discussed and demonstrated. Suggestions are made for sampling and scan strategies for the different analysis types.